2024
DOI: 10.1021/acsaelm.4c00208
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Red-Emitting OLEDs Prepared from Nona-Coordinated Europium(III) Complexes

Rashid Ilmi,
Xiaoyang Xia,
José D. L. Dutra
et al.

Abstract: We have designed and synthesized three nona-coordinated organoeuropium complexes (OEuCs) with the general formula [Eu(btfa)3(FurTerPy)] (Eu1), [Eu(btfa)3(ThioTerPy)] (Eu2), and [Eu(btfa)3(NapTerPy)] (Eu3) by employing a primary 4,4,4-trifluoro-1-phenyl-1,3-butanedione (btfa) antenna ligand and three functionalized 2,2′:6′,2″-terpyridine (TerPy) ligands bearing different electron-donating groups at the 4′ position, namely, FurTerPy = 4′-(furan-2-yl)-2,2′:6′,2″-terpyridine; ThioTerPy = 4′-(thiophen-2-yl)-2,2′:6′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Among the neutral ancillary ligands, tridentate terpyridine and its derivatives possessing higher binding affinities with metal ions than their bidentate counterparts can act as efficient Ln(III) emission sensitizers and organic linkers suitable for constructing efficient luminescent lanthanide complexes. , Recently, Ilmi et al found that the neutral [Eu(β-diketonate) 3 (terpyridine)] complexes displayed an outstanding electroluminescence (EL) performance that might find applications in the field of organic light-emitting diodes (OLEDs). , In our previous work, to investigate the synergistic sensitization effect of dual ligands and the influences of different substituents at the 4′-position of 2,2′:6,2″-terpyridine on the luminescence properties of Ln(III) center, the fluorinated β-diketone ligand, 1,1,1,5,5,5-hexafluoroacetylacetone (hfac) was chosen as primary ligand and 2,2′:6′,2″-terpyridine (tpy), 4′-phenyl-2,2′:6′,2″-terpyridine (ptpy) ligand with electron-withdrawing phenyl group and 4′-furan-2,2′:6′,2″-terpyridine (ftpy) with electron-donating furyl group at 4′-position were used as neutral ancillary ligands to construct mononuclear analogues [Ln(hfac) 3 (tpy)], [Ln(hfac) 3 (ptpy)], and [Ln(hfac) 3 (ftpy)]. , The solid-state photoluminescence lifetime (τ) and absolute quantum yield (QY) of these complexes were measured. The results suggest that terpyridine and its derivatives are good sensitizers for Eu(III), while hfac is a good sensitizer for Tb(III).…”
Section: Introductionmentioning
confidence: 99%
“…Among the neutral ancillary ligands, tridentate terpyridine and its derivatives possessing higher binding affinities with metal ions than their bidentate counterparts can act as efficient Ln(III) emission sensitizers and organic linkers suitable for constructing efficient luminescent lanthanide complexes. , Recently, Ilmi et al found that the neutral [Eu(β-diketonate) 3 (terpyridine)] complexes displayed an outstanding electroluminescence (EL) performance that might find applications in the field of organic light-emitting diodes (OLEDs). , In our previous work, to investigate the synergistic sensitization effect of dual ligands and the influences of different substituents at the 4′-position of 2,2′:6,2″-terpyridine on the luminescence properties of Ln(III) center, the fluorinated β-diketone ligand, 1,1,1,5,5,5-hexafluoroacetylacetone (hfac) was chosen as primary ligand and 2,2′:6′,2″-terpyridine (tpy), 4′-phenyl-2,2′:6′,2″-terpyridine (ptpy) ligand with electron-withdrawing phenyl group and 4′-furan-2,2′:6′,2″-terpyridine (ftpy) with electron-donating furyl group at 4′-position were used as neutral ancillary ligands to construct mononuclear analogues [Ln(hfac) 3 (tpy)], [Ln(hfac) 3 (ptpy)], and [Ln(hfac) 3 (ftpy)]. , The solid-state photoluminescence lifetime (τ) and absolute quantum yield (QY) of these complexes were measured. The results suggest that terpyridine and its derivatives are good sensitizers for Eu(III), while hfac is a good sensitizer for Tb(III).…”
Section: Introductionmentioning
confidence: 99%